2017
DOI: 10.20473/jbp.v19i3.2017.246-259
|View full text |Cite
|
Sign up to set email alerts
|

Ekstrak Etanol Moringa Oleifera Lam Terhadap Folikulogenesis Pada Mencit Model Endometriosis

Abstract: Endometriosis didefinisikan sebagai adanya jaringan endometrium di luar rahim.Peningkatan konsentrasi sitokin inflamasi dan faktor pertumbuhan di dalam cairanperitonium berkontribusi pada pembentukan lesi peritonium. Faktor pertumbuhanberperan selama folliculogenesis. Moringa oleifera kaya akan flavonoid. Kuercetin dankaempferol adalah flavonoid, senyawa dengan gugus hidroksil fenolik dengan aksiantioksidan yang memiliki kegunaan potensial terapeutik. Penelitian ini untukmembuktikan adanya pengaruh pemberian e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Regarding the ethanolic extract of Moringa Oleifera Lam on folliculogenesis in endometriosis model rats, the results showed that there was a significant difference (p<0.05) in the number of primary, secondary, tertiary and De Graff follicles in the control group and the treatment group with a dose of 0, 35 mg/gBW. The conclusion of the study showed that the ethanol extract of Moringa leaves increased folliculogenesis in endometriosis model rats [19] .…”
Section: Effect Of Moringa Leaf Water Extract (Moringa Oleifera) On T...mentioning
confidence: 89%
“…Regarding the ethanolic extract of Moringa Oleifera Lam on folliculogenesis in endometriosis model rats, the results showed that there was a significant difference (p<0.05) in the number of primary, secondary, tertiary and De Graff follicles in the control group and the treatment group with a dose of 0, 35 mg/gBW. The conclusion of the study showed that the ethanol extract of Moringa leaves increased folliculogenesis in endometriosis model rats [19] .…”
Section: Effect Of Moringa Leaf Water Extract (Moringa Oleifera) On T...mentioning
confidence: 89%
“…However, in mice with an endometriosis model, there was also an increase in folliculogenesis when Moringa leaf ethanol was administered at a dosage of 0.35 mg/kg BW. 10 A separate investigation carried out by Fathil demonstrated that Moringa enhances the concentrations of reproductive hormones (testosterone, luteinizing hormone, follicle stimulating hormone) in mice. 20 The main limitation of this study is in the production of the histological preparations.…”
Section: Diameter Of the Graafian Folliclesmentioning
confidence: 99%
“…Vitamin E acts as an antioxidant and enhances the production of steroid hormones during the oocyte maturation. 9,10 The increase of the follicle's antrum is a result of the proliferation of granulosa cells, leading to an increase in diameter of the follicle's basement membrane. The antrum is filled with fluid that contains the estrogen hormone secreted by the granulosa cells.…”
Section: Diameter Of the Graafian Folliclesmentioning
confidence: 99%
“…M. crenata leaves contain a high flavonoid, especially isoflavones formononetin and biochanin A, which have estrogenic activity and are important in folliculogenesis [13]. Furthermore, the ethanol extract of M. oleifera also contained a high flavonoid, such as quercetin and kaempferol, which could enhance folliculogenesis in mice with endometriosis [14]. To the best of our knowledge, the combination of M. crenata and M. oleifera leaves has never been used for improving folliculogenesis.…”
Section: Introductionmentioning
confidence: 99%